2020
DOI: 10.1128/aem.01768-20
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antivirulence Activity of Manuka Honey against Genetically Diverse Staphylococcus pseudintermedius Strains

Abstract: Staphylococcus pseudintermedius causes opportunistic infections in dogs. It also has significant zoonotic potential, with the emergence of multidrug-resistance leading to difficulty treating both animal and human infections. Manuka honey has previously been reported to inhibit many bacterial pathogens including methicillin resistant Staphylococcus aureus and is successfully utilised in both clinical and veterinary practice. Here we evaluated the ability of manuka honey to inhibit strains of S. pseudintermedius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…Selective binding ability of these polyphenols reduces Ag + ion to provide stability, greater exposed surface area and prevent agglomeration of the synthesised AgNPs 42 44 . Application of a combination of an antibiotic with an antibacterial-activity-enhancing agent (such as a plant extract), has been reported to be effective against antibiotic resistant bacteria in the new ‘combinational therapy’ 45 , 46 . Hence, we plan to explore combination of GA-AgNPs with different antibiotics in our future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Selective binding ability of these polyphenols reduces Ag + ion to provide stability, greater exposed surface area and prevent agglomeration of the synthesised AgNPs 42 44 . Application of a combination of an antibiotic with an antibacterial-activity-enhancing agent (such as a plant extract), has been reported to be effective against antibiotic resistant bacteria in the new ‘combinational therapy’ 45 , 46 . Hence, we plan to explore combination of GA-AgNPs with different antibiotics in our future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The health-promoting properties of honey are associated with plant secondary metabolites that are gathered by honey bees concomitant to the collection of flower nectars or Molecules 2021, 26, 1688. https://doi.org/10.3390/molecules26061688 https://www.mdpi.com/journal/molecules honeydew. In addition to its traditional household use as a sweetener, honey is often recognized as an alternative nutraceutical that exhibits a broad spectrum of in vitro activities such as antibacterial, antioxidant, anti-inflammatory, immunomodulatory, anticancer, anti-glycemic, prebiotic, and antiviral activities [1][2][3][4][5][6][7][8]. Correlated with honey's biological activities is the diversity of its secondary metabolite composition.…”
Section: Introductionmentioning
confidence: 99%
“…Other bioactive constituents such as organic acids, trace elements, vitamins, amino acids, and proteins were also found [1,2,19]. An abundance of information on the evaluation of honey's antimicrobial and antioxidant properties is available [3,7,8,16,20,23]. However, it is notable that the observed bioactivities are dependent on and as variable as the botanical and geographical origins, and climatic conditions [8][9][10][11]13,14,23].…”
Section: Introductionmentioning
confidence: 99%
“…As Manuka honey possesses an exceptional antibacterial activity, Brown et al tried it against Staphylococcus pseudintermedius which cause serious infections in domesticated animals and can be transmitted to their owner. They demonstrated that Manuka honey is not just effective against novel multidrug-resistant S. pseudintermedius isolates, but additionally works in tandem with clinically important antibiotics and reduces its virulence [49].…”
Section: Antibacterial Activity Of Bee Honeymentioning
confidence: 99%